Bridging the Gap between Medical Students and the Deaf-Mute Population - Sani, Huzairi; Zulkufli, Nada Syazana; Wahidah, Iman; Afiqah, Nurul; Sabrina, Nur; Farahiyah, Siti Nur (International Journal of Human and Health Sciences (IJHHS), 2021)
Introduction: Deafness is the inability to hear or impaired hearing. In 2018, more than 40,000 Malaysians were registered with hearing loss. Sign languages use visualization and facial expression to convey conversational meaning. However not many healthcare workers are able to converse in sign language thus hampering effective communication with deaf patients Objective: To evaluate the effectiveness of sign language in increasing awareness amongst medical students on healthcare access difficulties faced by the deaf. Methods: Four medical students underwent sign language classes at the Malaysian Federation of Deaf before being formally assessed and certified by an instructor. A video on common questions used in the clinical setting using sign language was then developed and shown to a cohort of 224 medical students in UiTM. Awareness on the importance of sign language amongst the cohort was surveyed before and after watching the video. The four medical students were also assessed on their awareness and communication proficiency before and after attending classes. Post- and pre-test responses were analysed using Wilcoxon signed rank test and paired sample T-test. Results: The number of students who were aware of the importance of sign language in the clinical setting increased from 39.7% (N=89) to 98.2% (N=220) after watching the video. The four medical students’ post-test scores also increased significantly after attending sign language classes (Mean +2.43, p<0.01). Significant improvement in basic knowledge of sign language and ability to demonstrate signs such as self-introduction and gathering medical history were observed (p=0.046). In totality, awareness of the challenges faced by deaf-mute patients when communicating with healthcare workers increased significantly (p=0.046). Conclusion: Sign language is essential in improving communication between deaf patients and healthcare workers. It is therefore imperative that healthcare personnel gain basic skills in sign language to improve communication and provide better medical services to the deaf community. International Journal of Human and Health Sciences Supplementary Issue: 2021 Page: S11